Prospective Clinical and Radiographic Results of Activ L Total Disk Replacement at 1- to 3-Year Follow-up. Issue 9 (November 2015) - Unknown
Abstract : Study Design: A prospective clinical study. Objective: To assess the clinical and radiographic results of activ L total disk replacement (TDR) on degenerative disk diseases. Summary of Background Data: There are few reports on Activ L TDR, and this is the first in China. Materials and Methods: From March 2009 to March 2012, 32 patients with degenerative disk disease underwent either monosegmental or bisegmental lumbar TDR, which was documented in a prospective observational mode. Clinical success was defined as disability [Oswestry Disability Index (ODI)] improvement of at least 15 points versus baseline, no device failure, no major complications, no neurological deterioration. Additional clinical parameters as Visual Analogue Scale and Oswestry Disability Index (ODI) were evaluated preoperatively and postoperatively (1, 2, and 3 y). Radiographic parameters as range of motion (ROM) and intervertebral disk height (IDH) of the index and adjacent segments were also carried out. Prosthesis subsidence and heterotopic ossification were observed during the follow-up period. Work status was tracked for all patients. Results: Overall, 30 patients (93.7%) were available for a mean follow-up of 28.8 months (12–46 mo) and had complete radiographic data. Their mean age was 45.1 years (32–58 y). At 3 years postoperatively, the success rate was 86.7% (26/30). After surgery, clinical parameters as Visual Analogue Scale score for back and leg pain, and ODI score showed statistically significant improvement ( P< 0.001), and the situation was well maintained during the follow-up time points. At 3 years postoperatively, the mean IDH at the index segment and upper and lower adjacent segments were 12.87, 12.61, and 11.62 mm, respectively, showing no significant difference compared with preoperative data ( P 1 =0.0597, P 2 =0.6669, P 3 =0.9813). The ROM of the index and upper adjacent segment showed a slight but significant increase at the 3-year follow-up compared with baseline ( P 1 =0.0128, P 2 =0.0007). The changes of ROM at the lower adjacent segment were not significant ( P =0.6637). Tears of the iliac vein were observed in 2 patients. Prosthesis subsidence was observed in 3 patients (1 at 12 mo postoperatively, 1 at 24 mo postoperatively, and 1 at 32 mo postoperatively). Heterotopic ossification was observed in 1 patient at 36 mo postoperatively. At the 3-year follow-up, only 8 patients went back to their original work, and 15 patients changed jobs, whereas the last 7 patients stopped working. Conclusions: The 1- to 3-year follow-up of this cohort of patients showed satisfactory clinical outcomes. The IDHs at index and adjacent segments were well maintained after the surgery. The ROM at the lower adjacent segment remained unchanged, but the ROM at the index and upper adjacent segments showed a slight increase. The long-term results of activ L TDR was to be investigated.